Principles or skeletons? Mabo and the discursive constitution of the Australian nation - P. Pether (Law Text Culture, 1998)
This essay is centred around what is arguably the most potentially constitutionally radical, and almost certainly the most politically contentious decision of the Australian High Court in its history. This is the 1992 Native Title Decision - Mabo v Queensland (No.2). My assessment of the potentially radical quality of the Mabo decision, constitutionally speaking, rests on what the judgment refuses to do and thus, paradoxically, makes imaginable, as much as on what it achieves. I will rehearse the decision briefly in order to suggest to readers the perspective from which this essay approaches it.